A Project-Based Approach to Ensuring the Competitiveness of a Region’s Tourism-Recreation Complex - LEVCHENKO, Tatyana Pavlovna; KORYAGINA, Evgeniya Victorovna; RASSOKHINA, Tatiana Vasilyevna; SHABALINA, Natalia Vladimirovna; LEBEDEVA, Olga Yevgenievna (Journal of Environmental Management and Tourism, 2019)
This paper is devoted to the development of a project-based approach to ensuring the competitiveness of a region’s tourism-recreation complex. The authors establish that a crucial factor is the efficiency of projects that have been implemented in regions already. It is proven that an indicator of the level of institutionalization of the public administration mechanism is the efficiency of mechanisms underlying the achievement of a balance of interests among all parties involved, which requires well-planned work on identifying the interests, coordinating those interests, and getting the partners involved in the process of implementation of the tourism project. The authors establish that currently work is being carried out in terms of putting in place mechanisms for public and private partnership, social services procurement, and social responsibility in the tourism sector. At the same time, institutionalizing the dialogue among entities associated with the mechanism for public administration of the development of a region’s tourism destination requires putting in place relevant infrastructure. The authors establish that developing a scientifically substantiated mechanism for public administration of the development of a region’s tourism destination requires analysis of the potential for developing regional destinations and factors for ensuring their competitiveness.